Anthropic use of soils around natural resources (Research, Society and Development, 2022)
Anthropic actions can impact natural resources positively, for example, environmental preservation programs, or negatively with the degradation of water and soils. Agricultural activities or urban expansion are totally dependent on anthropic interests and also cause environmental degradation to a greater or lesser degree. Therefore, the objective of this work was to provide an approach on the anthropic use of soils around natural resources. The search for scientific publications with emphasis on the present study was carried out on the Scielo and Google Scholar platforms. The information found was complemented with legislation on Permanent Preservation Areas (PPA). In this context, as a way of protecting environmental resources, the Forest Code was instituted, as an instrument that relates soil protection to the conservation of water resources. Despite being protected by environmental legislation, the occupation of PPA is increasing and the lack of environmental commitment on the part of society and little supervision on the part of public agents, provide advances in the degradation of these environments.